Can bank regulators use financial markets as indicators for supervisory intervention? : an event study analysis on the impact of earnings announcements on bank equity - Mothobi, Munyarari Bernard Simangaliso (School of Economics, 2014)
Includes bibliographical references (leaves 32-35).